Factors associated with receipt of a timely infant birth dose of hepatitis B vaccine at a tertiary hospital in North-Central Nigeria - Florence O. Bada; Kristen A. Stafford; Sophia Osawe; Eleanor Wilson; Nadia A. Sam-Agudu; Hegang Chen; Alash'le Abimiku; James D. Campbell (Public Library of Science (PLoS), 2022)
The World Health Organization recommends universal vaccination of medically stable infants with Hepatitis B vaccine within 24 hours of birth to prevent mother-to-child transmission of Hepatitis B virus (HBV) infection. However, the proportion of infants who receive a timely birth dose is extremely low in Nigeria. We reviewed the implementation of an infant HBV vaccine schedule at a single center and identified factors affecting the receipt of a timely birth dose of HBV vaccine. We conducted a retrospective cohort study utilizing data from the INFANT study, a 2013-2017 prospective cohort study of pregnant women with and without HIV and their infants We utilized bivariate and multivariable logistic regression to assess if maternal characteristics, or the day of the week on which the infant was born were significantly associated with timely receipt of a birth dose of HBV vaccine. Receipt of HBV vaccine on the day of birth or the following calendar day were considered a timely birth dose. Among 409 infants in our cohort, 133 infants (33%) received a timely birth dose of HBV vaccine. Only the day of the week on which infants were born was significant (p<0.0001): when compared to Friday, infants born Monday through Thursday had significantly higher odds of receiving a timely birth dose, while infants born on a Saturday or Sunday had similar (low) odds. We found no association between maternal age, education, marital status, HIV status, parity and mode of delivery, and infant receipt of a timely birth dose of HBV vaccine. National immunization programs could improve timely HBV birth dose rates by providing access to vaccine immediately following birth at all infant delivery venues on all days of the week. Where not possible, there should be rapid linkage to the nearest facility where HBV vaccination is immediately available.